Uma proposta de especifica??o funcional para constru??o de um gateway SIP/IPv6 como forma de obter suporte ? mobilidade na pr?xima gera??o de redes IP - Hisatugu, Wilian Hiroshi (2002)
Born of a military project, the internet is taking a prominent position in the daily life of people and companies, as a fundamental tool for the offer of new services and applications. However, these services and applications require that certain requirements be met for their perfect operation. That is, it needs quality of service (QoS) guarantees, which are not assured, by nature, by the IP protocol that is the basis of the internet. The possibility of remote access to network environments, along with the evolution of portable computers, has led to the emergence of the concept of mobile computing, or simply mobility, a feature not supported by the IP protocol. As a first option to support mobility, the mobile IP mechanism was proposed, which, due to its structure, causes an increase in the overhead of datagram processing, management and utilization, which may compromise network performance. The IPv6 protocol, a new version of the IP protocol, has some more favorable features to ensure QoS guarantees and mobility support, while maintaining a large processing effort for the IP routing network. Another very well-seen option to provide mobility support is the use of the SIP protocol. In order to make better use of the characteristics of these two protocols, a functional specification for the construction of a SIP / IPv6 Gateway is proposed as a way to obtain mobility support. As a form of validation of the presented proposal, two simulation models were constructed, using ARENA and COMNET III products. Finally, the main conclusions of the paper are presented and some suggestions for future work are pointed out.